2015
DOI: 10.5897/ajar2015.9844
|View full text |Cite
|
Sign up to set email alerts
|

Growth and gas exchange of okra under irrigation, organic fertilization and cover of soil

Abstract: The objective was to evaluate leaf area and gas exchange of okra plants for different irrigation depths, organic matter content and mulch. The activities were conducted in an experimental area of the State University of Paraíba, Campus IV, Catolé do Rocha-PB. An experimental design with randomized blocks, treatments distributed in a factorial 2 × 5 × 2 related to two irrigation levels, 100 and 50% of crop evapotranspiration (ETc), five levels of organic matter in the soil (1.8, 2.8, 3.8, 4.8 and 5.8%) and soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
1
2
0
1
Order By: Relevance
“…Moreover, soil mulch (SB and BS) had positive effect on the number of leaves (NL), statistically differing concerning the control treatment (Figure 1B). This result may be justified because plants without cover suffered higher evaporation due to greater soil exposure, which intensified the water loss, causing a water deficit and, consequently, reducing the number of leaves (Bertino et al, 2015). The present result conforms with obtained by Souza et al (2016), who showed a lower number of leaves of cowpea plants when grown without mulch.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, soil mulch (SB and BS) had positive effect on the number of leaves (NL), statistically differing concerning the control treatment (Figure 1B). This result may be justified because plants without cover suffered higher evaporation due to greater soil exposure, which intensified the water loss, causing a water deficit and, consequently, reducing the number of leaves (Bertino et al, 2015). The present result conforms with obtained by Souza et al (2016), who showed a lower number of leaves of cowpea plants when grown without mulch.…”
Section: Resultssupporting
confidence: 91%
“…Fertilization at planting was performed based on the supply of the sources and doses that were pre-established in the experimental design, which was provided 20 days before planting the sweet potato crop. For the calculation of the manure doses applied in the first experiment, the equation proposed by Bertino et al (2015) was adopted:…”
Section: Methodsmentioning
confidence: 99%
“…The beds were created 1.25 meters wide, 13 meters long and 0.20 meters high. Bovine manure was incorporated in the beds to raise the contents of organic matter from 1.15 to 3%, according to the formula proposed by Bertino et al (2015). The characterization of the cattle manure used in the beds is shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%